Comparison of Subjective Responses to Oral and Intravenous Alcohol Administration Under Similar Systemic Exposures. (28th February 2019) - Plawecki, Martin Henry; Durrani, Adnan Mahmood; Boes, Julian; Wetherill, Leah; Kosobud, Ann; O'Connor, Sean; Ramchandani, Vijay A.
Abstract : Background: Individuals perceive the effects of alcohol differently, and the variation is commonly used in research assessing the risk for developing an alcohol use disorder. Such research is supported by both oral and intravenous (IV) alcohol administration techniques, and any differences attributable to the route employed should be understood. Our objective was to test whether an individual's subjective responses to alcohol are similar when the breath alcohol concentration (BrAC) trajectory resulting from oral administration is matched by IV administration. Methods: We conducted a 2‐session, within‐subject study in 44 young adult, healthy, nondependent drinkers (22 females and 22 males). In the first session, subjects ingested a dose of alcohol which was individually calculated, on the basis of total body water, to yield a peak BrAC near 80 mg/dl, and the resulting BrAC trajectory was recorded. A few days later, subjects received an IV alcohol infusion rate profile, precomputed to replicate each individual's oral alcohol BrAC trajectory. In both sessions, we assessed 4 subjective responses to alcohol: SEDATION, SIMULATION, INTOXICATION, and HIGH; at baseline and frequently for 4 hours. We compared the individuals' baseline‐corrected responses at peak BrAC and at half‐peak BrAC on both the ascending and descending limbs. We also computed and compared Pearson‐product moment correlations of responses by route of administration, the Mellanby measure of acute adaptation to alcohol, and the area under the entire response curve for each subjective response. Results: No significant differences in any measure could be attributed to the route of alcohol administration. Eleven of 12 response comparisons were significantly correlated across the routes of alcohol administration, with 9 surviving correction for multiple measures, as did the Mellanby effect and area under the response curve correlations. Conclusions: The route of alcohol administration has a minimal effect on subjective responses to alcohol when an individual's BrAC exposure profiles are similar. Abstract : Individuals perceive the effects of alcohol differently, and the variation is used in both oral and intravenous alcohol research assessing the alcohol use disorder risk. Any differences attributable to the route of administration should be understood. Subjective responses obtained during an oral alcohol challenge were compared to those obtained during a subsequent intravenous alcohol challenge replicating the oral alcohol exposure trajectory. The route of alcohol administration has a minimal effect on subjective responses when an individual's exposure profiles are similar.